Conduct and reporting of citation searching in Cochrane systematic reviews: A cross‐sectional study. (4th July 2019) - Briscoe, Simon; Bethel, Alison; Rogers, Morwenna
Abstract : Background: The search for studies for a systematic review should be conducted systematically and reported transparently to facilitate reproduction. This study aimed to report on the conduct and reporting of backward citation searching (ie, checking reference lists) and forward citation searching in a cross section of Cochrane reviews. Citation searching uses the citation network surrounding a source study to identify additional studies. Methods: Cochrane reviews were identified by searching the Cochrane Database of Systematic Reviews using the wildcard symbol and date limiting to the 3‐month period November 2016 to January 2017. Cochrane reviews thus identified were screened for mention of citation searching. Descriptive detail on the conduct and reporting of citation searching was captured in data extraction forms and described and evaluated. Results: Two hundred fifteen Cochrane reviews were identified. One hundred seventy‐two reviews reported backward citation searching, and 18 reviews reported forward citation searching. Web of Science was the most frequently reported citation index. The studies used for backward citation searching consisted mainly of studies meeting the inclusion criteria. One‐third of reviews that reported forward citation searching used selected studies of importance. Reporting of citation searching was compliant with the Methodological Expectations of Cochrane Intervention Reviews (MECIR) standards, but full transparency requires additional detail that only a minority of reviews reported. Conclusion: The conduct of backward citation searching was more uniform than forward citation searching. This might be due to lack of MECIR guidance for forward citation searching. Reporting was generally compliant with MECIR, but this is not always sufficient to ensure full transparency.